2016
DOI: 10.1016/j.watres.2016.03.011
|View full text |Cite
|
Sign up to set email alerts
|

Significant role of UV and carbonate radical on the degradation of oxytetracycline in UV-AOPs: Kinetics and mechanism

Abstract: Carbonate radical (CO3(•-)), a selective oxidant, reacts readily with electron-rich compounds through electron transfer and/or hydrogen abstraction. In this study, the role of CO3(•-) in degrading oxytetracycline (OTC) by UV only, UV/H2O2 and UV/persulfate (UV/PS) advanced oxidation processes (AOPs) in the presence of HCO3(-) or CO3(2-) was investigated. For UV only process, the presence of photosensitizers, i.e., nitrate (NO3(-)) and natural organic matter (NOM), had different impacts on OTC degradation, i.e.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
56
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 252 publications
(59 citation statements)
references
References 65 publications
1
56
0
2
Order By: Relevance
“…Advanced oxidation processes based on Å OH or Å O 2 À have been commonly used in the degradation of persistent organic pollutants in water. For example, lots of technologies have been applied to generate Å OH or Å O 2 À radicals for aniline degradation including Fenton process [6,7], photocatalysis [8][9][10], catalytic wet oxidation [11][12][13], ozonation [14][15][16] and electrochemical oxidation [17][18][19][20]. However, these technologies have several limitations such as metal leaching, low pH rang (3)(4), excessive sludge production, and the high hydrogen peroxide transportation cost [1,4].…”
Section: Introductionmentioning
confidence: 99%
“…Advanced oxidation processes based on Å OH or Å O 2 À have been commonly used in the degradation of persistent organic pollutants in water. For example, lots of technologies have been applied to generate Å OH or Å O 2 À radicals for aniline degradation including Fenton process [6,7], photocatalysis [8][9][10], catalytic wet oxidation [11][12][13], ozonation [14][15][16] and electrochemical oxidation [17][18][19][20]. However, these technologies have several limitations such as metal leaching, low pH rang (3)(4), excessive sludge production, and the high hydrogen peroxide transportation cost [1,4].…”
Section: Introductionmentioning
confidence: 99%
“….... (7) .... (8) Effect of inorganic anions Many inorganic anions, such as CO 3 2-, HCO 3 -, NO 3 -, SO 4 2-, Cl -, could be present in textile effluents and hence significantly influence the removal of organic pollutants with AOP processes [14][15][16]. Among all anions, the influence of carbonate and bicarbonate are the most investigated ones, since they can be present in a significant amount both in surface waters and in wastewaters.…”
Section: Effect Of Organic Anionsmentioning
confidence: 99%
“…The overall reaction of nitrate photolysis can be presented by the reaction (11) . (14) Furthermore, it is reported that nitrite anions are very efficient • OH radicals scavengers (k = 1x10 10 M -1 s -1 ), unlike nitrates which are not so efficient (k < 1.0 x 10 5 M -1 s -1 ), and hence can negatively affect UV/H 2 O 2 treatments, particularly in the nitrate rich water (reactions (15) and (16) Decolorisation of RO16 dye by UV/H 2 O 2 process was conducted in the presence of 10, 50, and 100 mmol L -1 of nitrate. As shown in Fig 3. about 98% of 50 mg dm -3 RO16 dye was decolorized in the absence of nitrate, while in the presence of 10, 50, and 100 mmol L -1 of the nitrate the obtained percentage of decolorisation after 20 min of irradiation was 98%, 95%, and 85%, respectively.…”
Section: Effect Of Organic Anionsmentioning
confidence: 99%
“…In practical application, water quality and cost should be considered to determine initial pH. CO in UV/PS system was presented [7]. Different from the inhibition of …”
Section: Effect Of Phmentioning
confidence: 99%
“…However, it would inhibit the processes without UV or involving oxidants [4,7]. The inhibition mechanism of phosphates is (1) radical scavenging; (2) forming precipitate with metal ions, which covers the surface of catalyst.…”
mentioning
confidence: 99%